APossible Case of Filgrastim-Induced Death - V, Pawar; S.N, Krishna; G, Narayana; J, Sadiq; D, Thomas (Indian Journal of Pharmacy Practice)
This is a case report focusing on a 50 year old woman's death possibly due to Filgrastim. Filgrastim is considered to be a drug of choice in neutropenic cases. But in this case, Filgrastim has developed several severe Adverse Drug Reactions resulting into the death of patient. Naranjo's Causality Assessment Algorithm was used to assess the cause of death & the algorithm indicated Filgrastim as a possible cause of death.
Keywords: Filgrastim; Filgrastim-Induced Death; Drug-Induced Neutropenia & Granulocyte-Colony Stimulating Factor